2022
DOI: 10.1097/pas.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Myoepithelial Neoplasms on Acral Sites Show Distinctive and Reproducible Histopathologic and Immunohistochemical Features

Abstract: Cutaneous myoepithelial neoplasms are a heterogenous group of neoplasms with mixed tumors typically affecting the head and myoepitheliomas showing a predilection for the extremities. Their malignant counterparts, myoepithelial carcinoma, and malignant mixed tumor are exceptionally rare in the skin, and the morphologic criteria for malignancy are only poorly defined. The aim of the present study was to characterize the clinicopathologic features of myoepithelial neoplasms presenting on acral skin. The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Similarly, by analogy to their salivary counterpart, rearrangements of the PLAG1 gene have been identified in cutaneous mixed tumors, 33,34 as observed in our study that demonstrated TRPS1::PLAG1 fusion in 75% of the cases, with no morphologic differences in the nonrearranged case. It should be noted that although no cutaneous myoepithelial tumor lacking an epithelial component, that is, myoepithelioma, was included in our study, the recent series by Mehta et al 35 demonstrated immunohistochemical expression of PLAG in this setting, which could reflect a similar gene rearrangement.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, by analogy to their salivary counterpart, rearrangements of the PLAG1 gene have been identified in cutaneous mixed tumors, 33,34 as observed in our study that demonstrated TRPS1::PLAG1 fusion in 75% of the cases, with no morphologic differences in the nonrearranged case. It should be noted that although no cutaneous myoepithelial tumor lacking an epithelial component, that is, myoepithelioma, was included in our study, the recent series by Mehta et al 35 demonstrated immunohistochemical expression of PLAG in this setting, which could reflect a similar gene rearrangement.…”
Section: Discussionmentioning
confidence: 81%
“…At this anatomic location, cytologic atypia is common. Although most of these tumors follow an indolent clinical course, histopathologic features have not been shown to predict clinical outcomes, with some bland tumors eventually resulting in metastatic disease 11 …”
Section: Discussionmentioning
confidence: 99%
“…10 Characterization of cutaneous acral myoepitheliomas has recently been undertaken, and these neoplasms are generally characterized by sheets of epithelioid cells with prominent telangiectasia and a myxoid stroma. 11 At this anatomic location, cytologic atypia is common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one patient experienced a local recurrence 51 months after surgery, despite the initial excision being performed via a shave biopsy with a positive deep margin [ 3 ]. In contrast, some authors believe that histopathologic features appear to be a poor indicator of prognosis because some myoepitheliomas, of other variants than the syncytial one, develop metastasis, although with a benign morphological appearance [ 25 ]. In addition, there is a lack of evidence regarding the timing of follow-ups and the potential need for diagnostic investigations.…”
Section: Discussionmentioning
confidence: 99%